(untitled) - Moorhead, Gregory (Boston, 1992)
Organizational Behavior places core concepts of human behavior and industrial psychology in a real-world context. Strong end-of-chapter exercises, activities, plus an optional case and exercise book make this flexible text suitable for students at the undergraduate level. Likewise, the authors' emphasis on the latest organizational behavior research continues to attract graduate students.
Keywords: Organizational behavior,Hành vi tổ chức